A New Type-Reduction Algorithm for Type-2 Fuzzy Logic Controller (Damascus University Journal for engineering sciences, 2023)
Type-reduction is an important stage in the type-2 fuzzy logic controller, so improving the efficiency of this stage is momentous for developing the performance of the controller, and getting the best stability for the nonlinear engineering systems. We have published an article on comparing the most important algorithms used in type-reduction and showing the efficiency of KM and WM algorithms. In this article we combine between these two algorithms to propose a new algorithm that gives a greater accuracy and speed for the controller. And we achieved that by designing two type-2 fuzzy logic controllers for the cart and inverted pendulum system, and comparing the result of this new algorithm with KM and WM. As the new algorithm gave a better accuracy and speed than KM and WM, in the response of the studied system.
Keywords: Type-2 Fuzzy Sets; Inverted Pendulum; Fuzzy Control